ISOLATION AND BIOACTIVITY TEST OF SECONDARYMETABOLITES OF ENDOPHYTIC FUNGI FROM ONION BULBS(ALLIUM CEPA L.) AND CHILIES (CAPSICUM ANNUUM L.) - Rizky Prima, Sylvia
Endophytic fungi are believed to produce the secondary metabolites and have the same activity as their host plants. Exploration of endophytic fungi and their bioactivity is an interesting research topic in the search for new medicinal compounds. Among the plants commonly used by Indonesian people as traditional medicine are shallots and chilies. This research was conducted to isolate secondary metabolites and test the bioactivity of secondary metabolites from endophytic fungi isolated from onion bulbs (Allium cepa L.) and chilies (Capsicum annuum L.). Activity testing includes antioxidant activity tests and antimicrobial activity tests Five types of the endophytic fungi were isolated from onion and chili. Based on the results of molecular identification of endophytic fungal isolates from fruit of red chili, KCM 1 was identical to the species Diaporthe sp and KCM 2 identical to the species Chaetomium globosum. The results of molecular identification of endophytic fungal isolates from onion bulbs, endophytic fungal isolates KBM 1 was identical to the species Schizophyllum commune and KBM 2 identical to the genus Phlebia sp. The results of identification for endophytic fungal isolates from fruit of green chili (KCH 1) showed that the species was identical to Trametes hirsuta. Phylogenetic tree analysis was carried out with the BLAST program on the National Center for Biotechnology Information (NCBI). Phytochemical screening was carried out on the ethyl acetate extract of each endophytic fungus. The results of the phytochemical screening showed that all endophytic fungal contained flavonoids, phenols and steroids/triterpenoids. The results of the antioxidant activity test using the DPPH method of each ethyl acetate extract of the endophytic fungi Diaporthe sp, C. globosum, S. commune, Phlebia sp, and T. hirsuta showed that the highest antioxidant activity was obtained from the ethyl acetate extract of the endophytic fungus S. commune isolated from Allium cepa L. with an IC50 value of 3.15 ± 0.88 µg/mL and an AAI of 5.00 ± 1.34. In addition, antibacterial and antifungal activity tests have been carried out using the agar diffusion method to obtain inhibitory diameters and the microdilution method to obtain minimum inhibitory and killing concentrations. The test results showed that the ethyl acetate 5 extract of S. commune had potential as an antibacterial, especially for Gram-positive bacteria. Based on the results of antioxidant, antibacterial and antifungal activity tests, one selected extract was obtained which would proceed to the separation stage, namely the ethyl acetate extract of the endophytic fungus S. commune isolated from A. cepa L. The selected extract was then fractionated using vacuum liquid chromatography (KCV). From the KCV results, 9 combined fractions were obtained. Based on the qualitative antioxidant activity test by detecting the TLC DPPH spots, it was found that the combined fractions 4, 8 and 9 had dominant antioxidant spots. These results were supported by test results using DPPH which showed IC50 values of 1.85 ± 0.09; 2.04 ± 0.06 and 3.32 ± 0.34 µg/mL. Combined fractions 3–9 were tested for antibacterial activity using the agar diffusion and microdilution methods against Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, and Bacillus subtilis and obtained fractions 4 and 5 which had an inhibition zone > 10 mm with a minimum inhibitory concentration (MIC) value of 0.512 mg/mL against S. aureus bacteria which showed weak antibacterial potential. Based on the results above, the fraction F.8 was subfractionated using radial chromatography and eight (8) combined subfractions were obtained (SF. 8.1–SF. 8.8). TLC monitoring showed that SF. 8.5 looked almost pure and the activity test results showed that SF. 8.5 had antioxidant activity. SF 8.5 was purified using radial chromatography and to yield isolate K (10 mg). The results of the antioxidant activity test using the DPPH method obtained the IC50 value of isolate K of 0.40 ± 0.05 µg/mL and the AAI of 37.6 ± 4.95. Isolate K had better IC50 and AAI values than standard ascorbic acid. The results of the antibacterial activity test using the agar diffusion method with a test concentration of 20 µg/disk showed that isolate K did not have antibacterial activity. Furthermore, the characterization and identification of the structure of the active isolate was carried out using spectrophotodensitometry, RMI1H and 13C, and LCMS-MS. The results of data analysis showed that isolate K was 3,4-dihydroxybenzoic acid.